Homesteading a Pioneer Mental Health Court: A Judicial Perspective From the Last Frontier. (February 2013) - Trawver, Kathi R.; Rhoades, Stephanie L.
Although judges with interests in improving the criminal justice response to individuals with serious mental illness have long been principal leaders in the development and innovation of mental health courts (MHCs), little is known about the experiences of pioneering MHC judges. Through an edited written narrative, this article provides a history of one "first-generation" MHC through the lens of its founding judge. This chronicle of the Anchorage Mental Health Court's 15-year history details its inception and evolving challenges, triumphs, sustainability, and philosophy. The history of the Anchorage Mental Health Court, in the context of evolving national changes in MHC practices, is presented to inform both current and developing MHCs.